Plasma Levels of Keratinocyte Growth Factor Are Significantly Elevated for 5 Weeks After Minimally Invasive Colorectal Resection Which May Promote Cancer Recurrence and Metastasis - Shantha Kumara, H. M. C.; Shah, Abhinit; Miyagaki, Hiromichi; Yan, Xiaohong; Cekic, Vesna; Hedjar, Yanni; Whelan, Richard L. (Frontiers in Surgery, 2021)
Background: Human Keratinocyte Growth Factor (KGF) is an FGF family protein produced by mesenchymal cells. KGF promotes epithelial cell proliferation, plays a role in wound healing and may also support tumor growth. It is expressed by some colorectal cancers (CRC). Surgery's impact on KGF levels is unknown. This study's purpose was to assess plasma KGF levels before and after minimally invasive colorectal resection (MICR) for CRC. Aim: To determine plasma KGF levels before and after minimally invasive colorectal resection surgery for cancer pathology. Method: CRC MICR patients (pts) in an IRB approved data/plasma bank were studied. Pre-operative (pre-op) and post-operative (post-op) plasma samples were taken/stored. Late samples were bundled into 7 day blocks and considered as single time points. KGF levels (pg/ml) were measured via ELISA (mean ± SD). The Wilcoxon paired t-test was used for statistical analysis. Results: Eighty MICR CRC patients (colon 61%; rectal 39%; mean age 65.8 ± 13.3) were studied. The mean incision length was 8.37 ± 3.9 and mean LOS 6.5 ± 2.6 days. The cancer stage breakdown was; I (23), II (26), III (27), and IV (4). The median pre-op KGF level was 17.1 (95 %CI: 14.6–19.4; n = 80); significantly elevated (p < 0.05) median levels (pg/ml) were noted on post-op day (POD) 1 (23.4 pg/ml; 95% CI: 21.4–25.9; n = 80), POD 3 (22.5 pg/ml; 95% CI: 20.7–25.9; n = 76), POD 7–13 (21.8 pg/ml; 95% CI: 17.7–25.4; n = 50), POD 14–20 (20.1 pg/ml; 95% CI: 17.1–23.9; n = 33), POD 21–27 (19.6 pg/ml; 95% CI: 15.2–24.9; n = 15) and on POD 28–34 (16.7 pg/ml; 95% CI: 14.0–25.8; n = 12). Conclusion: Plasma KGF levels were significantly elevated for 5 weeks after MICR for CRC. The etiology of these changes is unclear, surgical trauma related acute inflammatory response and wound healing process may play a role. These changes, may stimulate angiogenesis in residual tumor deposits after surgery.